Low heterozygosity is associated with vector‐borne disease in crows. Issue 10 (5th October 2018) - Townsend, Andrea K.; Taff, Conor C.; Wheeler, Sarah S.; Weis, Allison M.; Hinton, Mitch G.; Jones, Melissa L.; Logsdon, Ryane M.; Reisen, William K.; Freund, David; Sehgal, Ravinder N. M.; Saberi, Mojan; Suh, Young Ha; et al.
Abstract: Infectious diseases can have devastating impacts on wildlife populations and are of particular concern for small, inbred populations. Identifying specific pathogens that are linked to morbidity and mortality in inbred individuals is a priority for the conservation of small populations, but opportunities to examine them in the wild are rare. Here, we examined the relationship between heterozygosity and infectious disease in American crows ( Corvus brachyrhynchos ), a species that engages in close inbreeding, focusing on three pathogens common in Davis, California, USA: West Nile virus (WNV), Plasmodium spp. (avian malaria), and Campylobacter jejuni . We found that low heterozygosity at a panel of 33 microsatellite loci was associated with two vector‐borne infectious diseases (WNV and avian malaria), but not with infection by the bacterial gut pathogen C. jejuni . Reasons for this association with vector‐borne pathogens are unclear, but might include behavioral factors and immunological differences associated with inbreeding. Overall, these data are consistent with the idea that inbred individuals may be more susceptible to both novel and endemic vector‐borne pathogens, underscoring the importance of protecting genetic diversity within populations and buffering small populations against infectious diseases.